A Systematic Review of Research Articles on Measurement Invariance in Education and Psychology - Betül Alatlı (International Journal of Assessment Tools in Education)
This study aims to reveal the trends in the related field by examining the researches evaluating the measurement invariance in education and psychology between 2008-2019. Accordingly, 99 articles published in three journals that were selected using the purposive sampling method among the journals indexed on Social Sciences Citation Index (SSCI)were analyzed within the scope of the study. As a result of the content analysis, in the studies investigating the measurement invariance, typical response tests were observed to be the most frequently employed tests, sample sizes often included 1501 or greater number of subjects, and data were mostly collected from students. The measurement invariance of the tests was mostly analyzed in terms of the gender variable. According to the results of the bibliometric analysis, on the other hand, only Multi-Group Confirmatory Factor Analysis was mostly conducted on the Mplus software package. In the studies, the most cited article was "Cheung and Rensvold (2002)", the author was "Cheung, G. W.", and the journal was "Structural Equation Modeling: A Multidisciplinary Journal". According to the results of the analysis, studies, references, and keywords including factor analysis were among the most commonly used group, which denotes that factor analysis has a crucial role in invariance measurement analyses.